Bioadsorbents produced from organic waste for dye removal: a review (Research, Society and Development, 2022)
The use of dyes in the textile industry triggers the contamination of its effluents and its disposal without prior treatment generates environmental impacts. For the immobilization and degradation of contaminating substances, the most efficient and selective technique is adsorption, where the dye molecules are removed when they adhere to the surface of the adsorbent. The use of low-cost materials from organic material residues, such as rice husk, sugarcane bagasse, corn cob, açaí seed, orange peel, fruit bagasse in general in natura or as activated carbon are great resources for removing unwanted substances. The purpose of the article is to present a literature review on the study of adsorbents from organic compounds.  The research was carried out in national and international journals, over the last six years, on activated carbon and biosorbent, with an efficiency of at least 70% in the removal of synthetic dyes.  In the information provided in the survey, most alternative adsorbent materials show high efficiency when compared to commercial coal or others, due to their good morphological properties. Regardless of the physicochemical treatments, the viability of the adsorbents is proven with the analyses carried out.